Factors associated with Myopia in school children in China: The Beijing Childhood Eye Study - You, Qisheng; Jonas, Jost B. (PLOS ONE, 2012)
Purpose To assess factors associated with myopia in school children in rural and urban parts of Greater Beijing. Methods The Beijing Pedriatic Eye Study was a population-based cross-sectional study, in which one school of each level (primary, junior high, senior high) was randomly selected from nine randomly selected districts out of 18 districts of Greater Beijing. The children underwent non-cylcoplegic refractometry and their parents an interview. Results Of 16,771 eligible students, 15,066 (89.8%) children (7,769 (51.6%) girls) participated, with 8,860 (58.8%) participants living in the rural region. Mean age was 13.2±3.4 years (range:7-18 years). In multivariate analysis, prevalence of myopia (defined as ≤−1.00 diopters) was associated with higher age (Odds ratio(OR):1.37; 95% confidence interval(CI):1.35,1.39), female gender (OR:1.35;95%CI:1.25,1.47), key school type (OR:0.77;95%CI: 0.70,0.85), higher family income (OR:1.04;95%CI:1.01,1.07), parental myopia (OR:1.46;95%CI:1.40,1.53), dim reading illumination (OR:0.93;95%CI: 0.88,0.98), longer daily studying duration (OR:1.10;95%CI:1.06,1.15), shorter duration of watching television (or computer) (OR:0.93;95%CI:0.89,0.97), higher self-reported protein intake (OR:0.94;95%CI:0.90,0.99), feeling well about life and status (OR:0.93;95%CI:0.89,0.98), and feeling tired or dizzy (OR:0.94;95%CI:0.91,0.97). Prevalence of high myopia (defined as ≤−6.00 diopters) was associated with higher age (OR:1.43;95%CI:1.38, 1.48), key school type (OR:0.61;95%CI:0.49,0.74), family income (OR:1.07;95%CI:1.02,1.13), parental myopia (OR:1.65;95%CI:1.54,1.76), dim reading illumination (OR:0.86;95%CI:0.77,0.96), less rest during studying (OR:1.18;95%CI:1.10,1.27), feeling well about life and studying (OR:0.88;95%CI: 0.81,0.96) and feeling dizzy or tired (OR:0.93;95%CI:0.87,0.99). Prevalence of high myopia (defined as ≤−8.00 diopters) was significantly associated with higher age (OR:1.39;95%CI:1.31,1.48;), key school type (OR:0.61;95%CI:0.42,0.88) and parental myopia (OR:1.87;95%CI:1.66,2.12). Conclusions Myopia in school children in Greater Beijing was associated with higher age, female gender, school type, parental myopia, higher socioeconomic background, dim reading illumination, longer daily studying duration, less rest during study, shorter duration of watching television (or computer), higher self-reported protein intake, feeling well about life and status, and feeling tired and dizzy.